How will persistent low expected returns shape household economic behavior?. (27th December 2018) - Horneff, Vanya; Maurer, Raimond; Mitchell, Olivia S.
Abstract: Many believe that global capital markets will generate lower returns in the future versus the past. We examine how persistently lower real returns will reshape work, retirement, saving, and investment behavior of older persons using a calibrated dynamic life cycle model. In a low return regime, workers build up less wealth in their tax-qualified 401(k) accounts versus the past, claim social security benefits later, and work more. Moreover, the better-educated are more sensitive to real interest rate changes, while the least-educated alter their behavior less. Interestingly, the distribution of wealth is more uniform in periods of persistent low expected returns.